Stem cell therapeutics for cancer - Shah, Khalid (Wiley Blackwell, 2013)
"Stem Cell Therapeutics for Cancer covers the application of stem cells in various cancers, with an emphasis on the aspects of these strategies that are critical to the success of future stem cell-based therapies for cancer. Topics covered in the book include stem cell sources, tumor specificity, targeted therapeutics, visualizing the stem cell, and therapeutic agent pharmacokinetics. Each chapter contains a brief introduction to the cancer, followed by an exploration of how engineered stem cells have been utilized to cure the disease in mouse models and in early phase clinical trials"--Publisher's description.